2022
DOI: 10.14202/vetworld.2022.841-847
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mesenchymal stem cell-conditioned medium gel on burn wound healing in rat

Abstract: Background and Aim: Stem cells are cells that can proliferate to form a new tissue, leading to its use in regenerative therapy. Stem cells will secrete biological factors, such as growth factors, cytokines, and other proteins to their surroundings and culture medium/conditioned medium (CM), altering tissue physiology. These factors can help wound healing, but their effect on third-degree burns is poorly understood. This research aimed to study the activity of mesenchymal stem cell-conditioned medium gel in hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“… 39 A recent study showed that adipose-derived stem cell CM could accelerate wound healing and hair growth in SD rats with burn wounds on the dorsal, but this study also did not reveal the mechanism of the treatment. 40 In the present study, HE and Ki67 staining suggested that the treatment of MSC-CM promoted the proliferation of skin tissue, CD31 staining suggested that the treatment promoted the proliferation of blood vessels and increased the local blood supply. Electron microscopy showed that the treatment promoted cell autophagy.…”
Section: Discussionsupporting
confidence: 58%
“… 39 A recent study showed that adipose-derived stem cell CM could accelerate wound healing and hair growth in SD rats with burn wounds on the dorsal, but this study also did not reveal the mechanism of the treatment. 40 In the present study, HE and Ki67 staining suggested that the treatment of MSC-CM promoted the proliferation of skin tissue, CD31 staining suggested that the treatment promoted the proliferation of blood vessels and increased the local blood supply. Electron microscopy showed that the treatment promoted cell autophagy.…”
Section: Discussionsupporting
confidence: 58%
“…Besides this, results use a measurement of the hydroxyproline levels as an index of collagen turnover (28) . The results show a signifi cant diff erence in hydroxyproline levels for the ethanol extract of cinnamon leaves and indicate an increase in breaking down granulation tissue from collagen maturation in injured skin (29,30) . CONCLUSION…”
Section: Resultsmentioning
confidence: 93%
“…This research calculated the sample size using “Power and Sample Size Calculation” application version 3.2.6 (Informer Technologies, Inc.). In previous studies, the average wound closure treated with MSC-CM was 67.03%, while that of the controls was 52.18% ( Laksmitawati et al ., 2022 ). With an alpha of 0.01, a power of 0.90, an SD of 8.38, and a difference of 15%, the required sample is 11 tails plus one tail for reserve.…”
Section: Methodsmentioning
confidence: 89%